Peran Kemitraan Agribisnis Petani Tebu dengan PG Rejo Agung Baru Madiun Jawa Timur - SIXMALA, MARDA; ANTARA, MADE; SUAMBA, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.3, Juli 2019, 2019)
The Role of the Sugarcane Farmer Agribusiness Partnership with Sugar Factory Rejo Agung Baru Madiun East Java The partnership that exists between sugarcane farmer with PG Rejo Agung Baru Baru is motivated by the demand and needs that can not be fulfilled by themselves. If seen from the benefits that can be achieved from sugar cane farmers’s participation in the partnership that is carried out by PG Rejo Agung Baru, they should have became more interested in participating this partnership. This study aims to understand and find out the partnership pattern implementation between PG Rejo Agung Baru and sugar cane farmers, the income comparison of partnered sugar cane farmers and non-partner sugar cane farmers, and also the constraints of this sugar cane agribusiness partnership.The ttest results of cash receipts, total revenues, cash costs, total costs, income cash costs and revenues from total costs show a pretty significant different result between partnered farmers and the non-partner ones. The constraints faced by partnered sugar cane farmers include low bargaining position, late disbursement of capital loan and also milling queue, while for non-partner sugar cane farmers, the constraint is the hard time during milling season, especially when no wholesaler wants to buy their sugar cane. As for PG Rejo Agung Baru themselves, the constrains circulate around the quality and quantity of raw sugar materials, sugar cane production from partnered farmers does not qualify MBS standard (Sweet, Clean, Fresh), sugar cane land that’s getting narrower each day, also the worker that’s getting rarer and requires high paid. Judging from the benefit income that partnered sugar cane farmers get from this partnership, the non-partner sugarcane farmers should have joint this partnership, because by joining, the nonpartner farmers can get a market guarantee, technical guidance, capital loans and also a much more competitive selling price instead of the price they got from the wholesaler.